Проблема професіогенезу особистості фахівця у зарубіжних концепціях - Мілорадова, Н. Е.; Miloradovа, N. E.; ORCID: http://orcid.org/0000-0002-0716-9736 (Право і безпека. – 2017. – № 2 (65). – С. 160–166, 2017)
Здійснено аналіз основних зарубіжних концепцій професіогенезу особистості фахівця. Розглянуто психотехнічні ідеї Г. Мюнстерберга та факторний підхід до вибору професійного шляху Ф. Парсонса, роль у виборі професії й професійного життя різних видів потреб у теоріях З. Фрейда, Е. Бордіна, Е. Роу та А. Маслоу, концепції У. Мозер, особливості розвитку особистості на різних етапах життєвого та професійного шляху в межах різних підходів (Ш. Бюлер, Дж. Сьюпер, Е. Ерікосон, Р. Хейвігхерст, Е. Гінзберг та Б. Лівехуд), типологічний підхід Д Холланда. Підкреслено, що більшість авторів розглядають професіогенез як інтеграцію двох процесів: розвитку особистості в онтогенезі, тобто на всьому життєвому шляху, і професіоналізації особистості з періоду початку професійного самовизначення до завершення активної трудової діяльності.

The author has analyzes the main foreign concepts of professional psychology of a specialist’s personality and stressed that the history of the development of the issue of professional psychology is the history of the formation of general scientific tendency of studying the problem of professional development and self-deployment of personality, where within its frames some “professional” theoretical and applied schools of professional psychology have been formed by today. The idea about labor and its significance for society were reflected in early Christian texts and philosophical theories. The greatest growth of ideas about labor education and professional training of children and youth in the West falls on the Renaissance in the XIV–XVI centuries (Thomas Moore, Tommaso Campanella, Ioannes Amos Comenius, John Locke). An indication of the beginning of the XX century was the growing relevance of the problem of professional development. The author has analyzed the main foreign theories of professional development, which most scholars combine in five main directions: 1) differential and diagnostic; 2) psychoanalytical; 3) the theory of decisions, 4) the theory of development; 5) typological direction. It has been determined that the most vulnerable moment within typological theories is the very principle, on the basis of which the construction of types is carried out. Besides, the real individual often does not meet any of the personality types associated with certain professional spheres. It has been emphasized that most authors consider professional psychology as an integration of two processes: the development of personality in ontogenesis that is, on the whole life path, and the professionalization of personality from the period of the beginning of professional self-determination to the completion of active labor activity.

Осуществлён анализ основных зарубежных концепций профессиогенеза личности специалиста. Рассмотрены психотехнические идеи Г. Мюнстерберга и факторный подход к выбору профессионального пути Ф. Парсонса, роль в выборе профессии и профессиональной жизни разных видов потребностей в теориях З. Фрейда, Е. Бордина, Е. Роу и А. Маслоу, концепции У. Мозер, особенности развития личности на разных этапах жизненного и профессионального пути в пределах разных подходов (Ш. Бюлер, Дж. Сьюпер, Е. Ерикосон, Р. Хейвигхерст, Е. Гинзберг та Б. Ливехуд), типологический подход Д Холланда. Подчёркнуто, что большинство авторов рассматривают профессиогенез как интеграцию двух процессов: развития личности в онтогенезе, то есть на всём жизненном пути, и профессионализация личности с периода начала профессионального самоопределения до завершения активной трудовой деятельности.
Проблема профессиогенеза личности специалиста в зарубежных концепциях
The problem of professional psychology of a specialist’s personality within foreign concepts
Мілорадова, Н. Е. Проблема професіогенезу особистості фахівця у зарубіжних концепціях / Н. Е. Мілорадова // Право і безпека. – 2017. – № 2 (65). – С. 160–166.
Мілорадова Н. Е. "Проблема професіогенезу особистості фахівця у зарубіжних концепціях." Право і Безпека 2 (2017): 160-166.
Miloradova, N.E. (2017), “The problem of professional psychology of a specialist’s personality within foreign concepts” [“Problema profesiohenezu osobystosti fakhivtsia u zarubizhnykh kontseptsiiakh”], Pravo i Bezpeka, No. 2, pp. 160–166.
Keywords: Психологія. Рsychology. Психология; Наукові публікації. Scientific publications. Научные публикации; професіогенез; професійний розвиток; зарубіжні концепції професійного становлення; фахівець; профессиогенез; профессиональное развитие; зарубежные концепции профессионального становления; специалист; professional psychology; professional development; foreign concepts of professional formation; specialist